PERAN SISTEM AKUNTANSI MANAJEMEN DALAM ORGANIZATIONAL LEARNING : Upaya Menghadapi Dinamika Organisasi - Faisal, Faisal; Rahayu, Dyah Sih (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2001)
The increasingly competitive markets and technological advancement have demend the practicioners and accedemicians to focused on interrelationship between corporate strategy and management accounting system (MAS). In management accounting the interdependent complexity of strategy, structure and systems are integrated through the concept of